The innovator’s dictionary : 555 methods and instruments for more creativity and innovation in your company - Aerssen, Benno van, 1964-; Buchholz, Christian (De Gruyter, 2020)
More and more people have to organize or moderate innovation processes, creative workshops and design thinking projects and need help when choosing appropriate tools. At the same time, the number of available methods has virtually exploded in recent years – making it difficult to find the most appropriate method. This book presents 555 of the most important innovation methods and tools, selected and curated by experienced innovation professionals. A step-by-step explanation for each method allows for easy implementation in your own team meeting or workshop. Further information on each method, such as method results, experience insights, required innovation skills and numerous illustrations help the reader to select the right instrument and adapt it to their respective goal. Whether you are a beginner or a professional, the book will help you to select methods quickly and safely. Innovation managers and everyone responsible for projects and products will find invaluable help for their work in this dictionary. It also offers a Design Thinking reference for all methods as well as a free online method search with various search paths. Check out our webinar on this book. The editors discuss and present the use of tools and innovation methods in workshops, meetings and innovation projects: https://www.youtube.com/watch?v=TZNdWiY_s2w&list=PLfcENNPixVmPIAdYVgenuuX3NSBzWPUxV&index=6